Multiple origins of prokaryotic and eukaryotic single-stranded DNA viruses from bacterial and archaeal plasmids - Kazlauskas, Darius; Varsani, Arvind; Koonin, Eugene V.; Krupovic, Mart (Nature communications, 2019)
Single-stranded (ss) DNA viruses are a major component of the earth virome. In particular, the circular, Rep-encoding ssDNA (CRESS-DNA) viruses show high diversity and abundance in various habitats. By combining sequence similarity network and phylogenetic analyses of the replication proteins (Rep) belonging to the HUH endonuclease superfamily, we show that the replication machinery of the CRESS-DNA viruses evolved, on three independent occasions, from the Reps of bacterial rolling circle-replicating plasmids. The CRESS-DNA viruses emerged via recombination between such plasmids and cDNA copies of capsid genes of eukaryotic positive-sense RNA viruses. Similarly, the rep genes of prokaryotic DNA viruses appear to have evolved from HUH endonuclease genes of various bacterial and archaeal plasmids. Our findings also suggest that eukaryotic polyomaviruses and papillomaviruses with dsDNA genomes have evolved via parvoviruses from CRESS-DNA viruses. Collectively, our results shed light on the complex evolutionary history of a major class of viruses revealing its polyphyletic origins. Most single-stranded DNA viruses have small genomes replicated by rolling circle mechanism which is initiated by the Rep protein. Here, using sequence similarity network and phylogenetic analyses, Kazlauskas et al. show that viral Reps evolved from Reps of bacterial and archaeal plasmids on multiple independent occasions.